Design and Development of an Integrated Automation Simulation System - Gomez, Wilfreg Ralph Gonzales (International Journal of Integrated Engineering, 2019)
An efficient simulation process comprises of an essential set of technological tools and approaches for the successful implementation of optimized manufacturing since it allows the makers for the trialing and validation of product, process, system design, and configuration. It also strives to engage the user completely within an experimental context, thereby greatly enhancing the overall impact through efficient use of time, workforce, and a thoroughly saved cost. Just as science further develop tools to rapidly progress the quality of commercial products, the technology transfer on the development of manufacturing systems also advances thereby creating an equal opportunity and need for different specialists to maintain these systems. These specialist are the engineers that come from the various sectors of academe and industry in which there is a great need for expertise synchronization to achieve balance in the technology acceptance.  This paper gives an highlight of the different applications of testing, drilling, clamping, and ejecting process in manufacturing industries and proposes an efficient design of a digital automation simulation system that emulates the engineering control techniques in operating a testing, drilling, clamping, and ejecting process thereby serves as an instrument for the development of 21st century learning and automation technology adaptation.